Synthesis of 1,2-dialkylaminoethers via photoredox catalyzed hydroamination of vinylethers - Niggli, Nadja Elena; Bienewald, Frank; Kirchner, Hülya; Shevchenko, Grigory A.; Hashmi, A. Stephen K.; Schaub, Thomas (ChemistrySelect, 2023)
Herein, a general applicable method for the atom-economic catalytic construction of a broad range of 1,2-dialkylaminoethers is presented. By taking advantage of an elaborated protocol for the photocatalyzed anti-Markovnikov selective hydroamination of nonactivated alkenes, a series of 1,2-dialkylaminoethers was accessed by reacting readily available vinyl ethers with secondary alkyl amines. It was demonstrated that the reaction can be performed at low catalyst loadings while the commonly employed triisopropylbenzene thiol Hydrogen Atom Transfer (HAT)-catalyst was replaced by an easier accessible mesityl thiol. Furthermore, the inexpensive and readily available diphenyl disulfide was proven as suitable HAT-catalyst alternative for the efficient hydroamination of simple vinyl ethers.